The moonstone [videorecording (DVD)] - Bierman, Robert; Wise, Greg, 1966-; Sher, Antony, 1949-; Hodge, Patricia, 1946-; Vaughan, Peter, 1923-2016; Jeffrey, Peter, 1929-1999; Hawes, Keeley, 1976-; Collins, Wilkie, 1824-1889 (WGBH Boston Video, 2005)
A stolen Hindu diamond, the Moonstone, works its curse after being stolen from it's shrine. Just before Rachel's birthday, a man named Franklin Blake announces to Rachel that the Moonstone has been bequeathed to her by Herncastle. Blake gives her the jewel on her birthday and offers to mount the jewel for her to wear. The jewel goes missing and Rachel believes that Blake stole it. Determined to prove his innocence, Blake leaves in order to pursue the real truth behind the theft.